THE ACMEOLOGICAL APPROACH TO THE DEVELOPMENT OF FUTURE TEACHERS’ PROFESSIONAL ACTIVITY (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This scientific study deeply analyzes the theoretical and practical aspects of applying the acmeological approach in the development of future teachers' professional activities. Acmeology, as a science that explores the highest stages of personal development, is integrated into the pedagogical process to support the enhancement of personal and professional competencies among prospective educators.